The challenges in enforcing post divorce order of native court in East Malaysia - Mohd Zin, Najibah; Abdul Hak, Nora; Che Soh @ Yusoff, Roslina; Md Hashim, Noraini; Ambaras Khan, Hanna; Md Said, Muhamad Helmi (2018)
The native court in Malaysia comprises of Mahkamah Anak Negeri Sabah and Mahkamah Bumiputera Sarawak. Their existence is recognised by the Malaysian Government and their rights are mentioned in the Federal Constitution of Malaysia. Despite the facts that these courts are given power and authority in dealing with the personal law of the native in each state, there are challenges in enforcing orders of post-divorce of these courts. This paper is significant since there is no such study done yet under this topic. The objectives of this paper are to study the enforcement of post-divorce order in native court in East Malaysia, to examine the problems and challenges facing by the divorcees in enforcing the divorce’s order and make recommendation in overcoming them as to improve the current system. This paper adopts library-based and qualitative research method which consists of group discussion and interview of the village headman (ketua kampung) headman (penghulu), community leader, native courts’ judges, native court of appeal’s judge, registrar of native court and divorcees. The result of this research showed that there are four challenges that need to be addressed. First, the husband could not be found upon the issuance of the divorce order; second, husband’s default payment of maintenance; third, lack of man power and lastly, husband convert to Islam. Thereafter, this paper suggests the States government to assist the court by providing bailiff or enforcement body, increase funding and to create a department or body in assisting the divorcee to enforce the divorce order.